Representasi Stereotype Laki-laki dalam Lirik Lagu The Lucky Lacky “Aku Bukanlah Superman” - Luthfi Hanif Fakharoenvissa; Rini Sulastri (Gunung Djati Conference Series, 2024)
Music is an expression of feelings expressed through writing and tones. This article explores the relationship between music, gender, and social representation in song lyrics, with a focus on the song "I'm Not Superman." In addition, this article tries to understand how local values influence gender ideas in the Indonesian cultural context. The research method used is descriptive qualitative with analysis of song lyrics as a data source. The research results show that the lyrics of this song explore the humanity and vulnerability of a man, challenging the stigma of traditional masculinity. There are stereotypical gender roles reflected in society, which expect men to remain strong and restrain their emotions. In the lyrics of the song, the singer may be trying to celebrate human vulnerability and diversity, as well as challenge gender norms that give rise to certain stigmas. The analysis also looks at the representation of men in song lyrics, where fathers are the main actors who provide education and rules to children, giving rise to the construction of stigma against men. It is hoped that this research will increase awareness of the role of music in gender Stereotype and spark discussion about positive gender representation in music media.